The brain box the essential guide to success at school or college - Hodgson, David; Benton, Tim (Carmarthen, Wales, UK Independent Thinking Press, 2014)
The Brain Box ? a personal journal for each student to be their best at school ? boost grades, improve motivation, memory, learning and understanding, exam techniques. It will help teachers prove they apply many Ofsted guidelines, but will also appeal to parents. By using Neuro Linguistic Programming and explaining neuroscience the authors take students on their journey from building their profile to looking at what motivates them, their ambitions, and their future goals. Case studies, anecdotes of 'success'/motivation are littered throughout and questions are posed to get students thinking.
Keywords: Attention -- Study and teaching; Brain; Cognition; Learning, Psychology of; Listening -- Study and teaching; Study skills; Neurolinguistic programming